2006
DOI: 10.1007/s11768-006-4199-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for Cohen-Grossberg neural networks with multiple delays

Abstract: The stability analysis of Cohen-Grossberg neural networks with multiple delays is given. An approach combining the Lyapunov functional with the linear matrix inequality (LMI) is taken to obtain the sufficient conditions for the globally asymptotic stability of equilibrium point. By using the properties of matrix norm, a practical corollary is derived. All results are established without assuming the differentiability and monotonicity of activation functions. The simulation samples have proved the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In reality, during the implementation of artificial neural networks on very large scale integrated circuit, transmitting time delays due to the finite switching speed of amplifiers are unavoidable and may lead to instability and oscillation in a neural network. For this reason, some works have shown that time delays should be incorporated into the model equations of the network (for example, [8][9][10][11][12][13]). In [8], Cao and Liang proposed a Cohen-Grossberg neural network with time-varying delays.…”
mentioning
confidence: 99%
“…In reality, during the implementation of artificial neural networks on very large scale integrated circuit, transmitting time delays due to the finite switching speed of amplifiers are unavoidable and may lead to instability and oscillation in a neural network. For this reason, some works have shown that time delays should be incorporated into the model equations of the network (for example, [8][9][10][11][12][13]). In [8], Cao and Liang proposed a Cohen-Grossberg neural network with time-varying delays.…”
mentioning
confidence: 99%